Arbidol (Umifenovir): A Broad-Spectrum Antiviral Drug That Inhibits Medically Important Arthropod-Borne Flaviviruses - Haviernik, Jan; Štefánik, Michal; Fojtíková, Martina; Kali, Sabrina; Tordo, Noël; Rudolf, Ivo; Hubálek, Zdeněk; Eyer, Luděk; Ruzek, Daniel (Viruses, 2018)
Arthropod-borne flaviviruses are human pathogens of global medical importance, against which no effective small molecule-based antiviral therapy has currently been reported. Arbidol (umifenovir) is a broad-spectrum antiviral compound approved in Russia and China for prophylaxis and treatment of influenza. This compound shows activities against numerous DNA and RNA viruses. The mode of action is based predominantly on impairment of critical steps in virus-cell interactions. Here we demonstrate that arbidol possesses micromolar-level anti-viral effects (EC50 values ranging from 10.57 ± 0.74 to 19.16 ± 0.29 µM) in Vero cells infected with Zika virus, West Nile virus, and tick-borne encephalitis virus, three medically important representatives of the arthropod-borne flaviviruses. Interestingly, no antiviral effects of arbidol are observed in virus infected porcine stable kidney cells (PS), human neuroblastoma cells (UKF-NB-4), and human hepatoma cells (Huh-7 cells) indicating that the antiviral effect of arbidol is strongly cell-type dependent. Arbidol shows increasing cytotoxicity when tested in various cell lines, in the order: Huh-7 < HBCA < PS < UKF-NB-4 < Vero with CC50 values ranging from 18.69 ± 0.1 to 89.72 ± 0.19 µM. Antiviral activities and acceptable cytotoxicity profiles suggest that arbidol could be a promising candidate for further investigation as a potential therapeutic agent in selective treatment of flaviviral infections.
Keywords: Animals; Antiviral Agents; Indoles; regulace exprese virových genů; Chlorocebus aethiops; umifenovir; indoly; buněčné linie; cytotoxicity; Inhibitory Concentration 50; flavivirus; Viral Envelope Proteins; antivirové látky; Vero Cells; Flavivirus Infections; lidé; Arthropod Vectors; Flavivirus; Vero buňky; Gene Expression Regulation, Viral; inhibiční koncentrace 50; viry klíšťové encefalitidy; Zika Virus; Cell Line; virus zika; Encephalitis Viruses, Tick-Borne; antiviral activity; arbidol; proteiny virového obalu; členovci - vektory; West Nile virus; cell-type dependent antiviral effect; Cercopithecus aethiops; Cell Survival; zvířata; infekce viry z rodu Flavivirus; viabilita buněk; virus západního Nilu; Humans